The maturation of exploratory behavior in adolescent Mus spicilegus on two photoperiods - Cryns, Noah G.; Lin, Wan Chen; Motahari, Niloofar; Krentzman, Oliver J.; Chen, Weihang; Prounis, George; Wilbrecht, Linda (Frontiers in Behavioral Neuroscience, 2022)
Dispersal from the natal site or familial group is a core milestone of adolescent development in many species. A wild species of mouse, Mus spicilegus, presents an exciting model in which to study adolescent development and dispersal because it shows different life history trajectory depending on season of birth. M. spicilegus born in spring and summer on long days (LD) disperse in the first three months of life, while M. spicilegus born on shorter autumnal days (SD) delay dispersal through the wintertime. We were interested in using these mice in a laboratory context to compare age-matched mice with differential motivation to disperse. To first test if we could find a proxy for dispersal related behavior in the laboratory environment, we measured open field and novel object investigation across development in M. spicilegus raised on a LD 12h:12h light:dark cycle. We found that between the first and second month of life, distance traveled and time in center of the open field increased significantly with age in M. spicilegus. Robust novel object investigation was observed in all age groups and decreased between the 2nd and 3rd month of life in LD males. Compared to male C57BL/6 mice, male M. spicilegus traveled significantly longer distances in the open field but spent less time in the center of the field. However when a novel object was placed in the center of the open field, Male M. spicilegus, were significantly more willing to contact and mount it. To test if autumnal photoperiod affects exploratory behavior in M. spicilegus in a laboratory environment, we reared a cohort of M. spicilegus on a SD 10h:14h photoperiod and tested their exploratory behavior at P60-70. At this timepoint, we found SD rearing had no effect on open field metrics, but led to reduced novel object investigation. We also observed that in P60-70 males, SD reared M. spicilegus weighed less than LD reared M. spicilegus. These observations establish that SD photoperiod can delay weight gain and blunt some, but not all forms of exploratory behavior in adolescent M. spicilegus.